Comparison of Conventional Plate Assays with DNA-based Screening Protocols for Protease and Cellulase Production from Putative Bacillus Isolates - Rañoa, Diana Rose; Lumibao, Candice; Roxas, Jennifer; San Luis, Boris; Hedreyda, Cynthia (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Putative Bacillus isolates obtained from mud and soil samples of Mt. Makiling, Los Baños, Laguna were screened for the production of either cellulase or alkaline protease using cellulose and casein plate assays, respectively. Five out of eight isolates assayed for cellulase activity tested positive. DNA from these eight samples were extracted using the modified ROSE method for slot blot hybridization with cellulase gene probe. Out of the five samples positive for the cellulose plate assay, only three exhibited hybridization results. DNA from the eight isolates were used as templates for PCR amplification using primers specific for B. subtilis cellulase gene. Out of the eight isolates, two produced the expected 350-bp cellulose amplicon. Another set of ten putative Bacillus isolates were screened for the production of alkaline protease using casein plate assay. Four isolates exhibited protease activity. Genomic DNA extracted from ten isolates were subjected to slot blot hybridization using a fragment of alkaline protease gene from B. pumilus. Five isolates, of which four previously tested positive for protease activity, showed positive hybridization signals. PCR analysis using primers designed based on alkaline protease gene of B. pumilus showed that only one isolate produced the expected 320-bp PCR amplicon. These data suggest that biochemical plate assays may be advantageous for isolating bacteria that produce different types of cellulose and alkaline protease, while DNA-based methods are useful in detecting specific target genes but may therefore miss out on novel or variant enzymes.